THE POWER OF NETIZENS ATAS KEPOPULERAN THREAD KKN DI DESA PENARI - Maisyaroh Febriana Putri; Rianna Wati (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2023)
The thread KKN di Desa Penari, which was written by the SimpleMan Twitter account, has recently been the subject of discussion in cyberspace. This article focuses on the topic of netizens' reception of the KKN di Desa Penari thread, which was written by the SimpleMan account on Twitter social media. This research uses qualitative research. The material object of this research is the KKN di Desa Penari thread from SimpleMan's Twitter account. The formal object of this research is the comments of netizens in the thread. The research data is the contents of the thread, netizens' reception of the thread, and various information related to the research topic. Data interpretation techniques are carried out by uncovering how netizen responses can influence the popularity of the thread by using literary reception theory. The theory of literary reception has two basic concepts, namely horizon of expectation' and 'open space'. These two things form the basis for understanding the theory of literary reception. The phenomenon of 'the power of netizens' turned out to be very influential in the popularity of threads written by the SimpleMan Twitter account KKN di Desa Penari. This horror genre thread has succeeded in gaining popularity and trending # 1 on Twitter social media. Keywords: KKN di Desa Penari, the power of netizens, literary reception